2017
DOI: 10.1007/s00420-017-1209-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory effects and biomarkers of inflammation due to welding-derived nanoparticle aggregates

Abstract: PurposeWelders are exposed to airborne particles from the welding environment and often develop symptoms work-related from the airways. A large fraction of the particles from welding are in the nano-size range. In this study we investigate if the welders’ airways are affected by exposure to particles derived from gas metal arc welding in mild steel in levels corresponding to a normal welding day.MethodIn an exposure chamber, 11 welders with and 10 welders without work-related symptoms from the lower airways an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
(49 reference statements)
0
13
0
1
Order By: Relevance
“…In this study, we observed the effects on the proteome level in the nasal region after exposure to welding fumes. Proteins with changed levels were detected following welding fume particle exposure compared to filtered air, although neither clinical symptoms nor specific pro-inflammatory markers in nasal lavage were recorded in the study subjects [ 18 ]. This suggests that by applying a more comprehensive proteomic analysis, important biological information might still be gained even if no clinical symptoms can be recorded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we observed the effects on the proteome level in the nasal region after exposure to welding fumes. Proteins with changed levels were detected following welding fume particle exposure compared to filtered air, although neither clinical symptoms nor specific pro-inflammatory markers in nasal lavage were recorded in the study subjects [ 18 ]. This suggests that by applying a more comprehensive proteomic analysis, important biological information might still be gained even if no clinical symptoms can be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…However, these suggestions have to be further studied because there is a possibility of leakage from the circulation as result of exposure-related tissue damage. A previous study [ 18 ] of a symptomatic welding group showed that they had an increasing trend of blood neutrophils after exposure and that they had a tenfold higher level of exhaled breath condensate leukotriene B4 compared to the other groups. Leukotrienes use lipid signaling to convey information order to regulate immune responses, and leukotriene B4 is involved in inflammation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, exposure to nanoparticle‐rich welding fumes (1 mg m −3 intermittently for 3 s every 20 min for 5.5 h) in a chamber setting led to mild increases in IL‐6 in the nasal lavages of welders without lower airways symptoms, whereas there were no significant changes in lung function or blood biomarkers. [ 104 ] To the best of our knowledge, we are aware of only a two sets of experiments that have performed inhalation exposures to a MNM of potentially greater toxicity (excluding combustion‐derived particle studies), both using zinc oxide nanoparticles. [ 105–108 ] Beckett et al.…”
Section: Controlled Exposures In Human Volunteersmentioning
confidence: 99%